Field Dynamics Faced by Community Health Workers During a Public Health Crisis: A Qualitative Study of Motivations and Challenges - Syamsir, Syamikar Baridwan; Setiawan, Agus; Permatasari, Henny; Supriyatno, Heru; Yudanagara, Bani Bacan Hacantya; Nrul Huda (Window of Health : Jurnal Kesehatan, 2025)
The global shortage of healthcare professionals has intensified efforts to train more Community Health Workers (CHWs) to meet health and developmental needs. Amidst a global health crisis, such as the COVID-19 pandemic tragedy that occurred several years ago, CHWs have played a crucial role in controlling community-based outbreaks, thereby strengthening the public health emergency response while facing numerous challenges. This study explores the motivations and challenges CHWs face in managing health crises. Employing a descriptive phenomenological approach, this study conducted semi-structured in-depth interviews with 13 CHWs in Makassar City, selected through purposive sampling. Data were analyzed using thematic analysis via the Colaizzi method. Thematic analysis revealed three main themes and seven sub-themes, encapsulating factors of social needs and expanded health perspectives as motivational elements alongside challenges such as the prevailing negative paradigm regarding the health crisis. CHWs are instrumental in spearheading community-based activities to manage health crises. CHW training programs, facilitated by community nurses, can significantly improve their performance and impact within the community.